2018
DOI: 10.1002/ejoc.201800283
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic β‐Cyclodextrin Dimers for Squaraine Binding: Effect of Host Architecture on Photophysical Properties, Aggregate Formation and Chemical Reactivity

Abstract: Reported herein is the synthesis and application of three novel β‐cyclodextrin dimer hosts for the complexation of near infrared (NIR) squaraine dyes in aqueous solution. A series of eight different N‐substituted N‐methyl anilino squaraine dyes with variable terminal groups are investigated, with an optimal n‐hexyl‐substituted squaraine guest demonstrating binding constants orders of magnitude higher than the other squaraine–host combinations and comparable to literature‐reported systems. Moreover, hydrophobic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…Recent reports from our research groups have focused on the design, optimization, and sensing applications of cyclodextrin complexes (for the Levine group) (Serio et al, 2015 ; Chaudhuri et al, 2018 ; Haynes et al, 2019 ), and on the engineering, deployment, and evaluation of water purification filters (for the Boving group) (Schifman et al, 2016 ; Eberle et al, 2017 ; Blanford et al, 2018 ), which combined have provided us with unique insight into the potential of cyclodextrins to benefit the water purification process. Reported herein are the results of our investigations into the effect of α-cyclodextrin complexation on chlorine dioxide-based water treatment, and how such complexation affects the quantity and distribution of degradation byproducts.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports from our research groups have focused on the design, optimization, and sensing applications of cyclodextrin complexes (for the Levine group) (Serio et al, 2015 ; Chaudhuri et al, 2018 ; Haynes et al, 2019 ), and on the engineering, deployment, and evaluation of water purification filters (for the Boving group) (Schifman et al, 2016 ; Eberle et al, 2017 ; Blanford et al, 2018 ), which combined have provided us with unique insight into the potential of cyclodextrins to benefit the water purification process. Reported herein are the results of our investigations into the effect of α-cyclodextrin complexation on chlorine dioxide-based water treatment, and how such complexation affects the quantity and distribution of degradation byproducts.…”
Section: Introductionmentioning
confidence: 99%
“…Significant structural dependency has been seen previously for squarainecyclodextrin systems, in which small changes in the structure of a squaraine fluorophore dramatically effects its ability to bind in β-cyclodextrin hosts. This was shown both by our group, studying the interaction between differentially substituted squaraine fluorophores and β-cyclodextrin dimers, [32] and other groups, who showed that binding of squaraine in β-cyclodextrin, predominantly in 1 : 2 squaraine: cyclodextrin complexes, led to strong complex formation and marked changes in the photophysical activity. [33] Differences in affinities of the squaraine fluorophores for the cyclodextrin scaffold, in turn, can easily translate into differences in the observed cyclodextrinpromoted energy transfer.…”
Section: Quantification Of Analyte Donor (1-5) To Squaraine Acceptor mentioning
confidence: 68%
“…Squaraine dyes were synthesized using previously reported methods, with spectral analysis of all intermediates and the final products matching literature-reported spectra. [32] Instrumentation: FTIR spectra of cellulose and β-cyclodextrinfunctionalized cellulose were obtained using a Shimadzu IRAffinity-1S FTIR spectrometer with Miracle 10 single reflection ATR accessory or a Thermo Electron Corporation Nicolet 380 FTIR spectrometer with Smart Orbit diamond ATR accessory. The calibration curve used to calculate the cyclodextrin functionalization density was created using a Shimadzu UV-3600 Plus spectrophotometer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Levine and her group are interested in the use of cyclodextrin‐based supramolecular systems to solve problems in the areas of sensor development and molecular recognition. She has reported in the European Journal of Organic Chemistry on supramolecular hosts for benzo[ a ]pyrene binding and detection, and on β‐cyclodextrin dimers for squaraine binding …”
Section: Awarded …mentioning
confidence: 99%